Agglomerationen mit nutzergenerierten Inhalten neu definiert Visualisierung der Nordostschweiz mithilfe von Wikipedia. - Bruggmann, André; Salvini, Marco M.; Fabrikant, Sara I. (Routledge, 2013)
Die Arbeit testet das Potential einer zur Volkszählung alternativen Datengrundlage. Dabei besteht nicht der Anspruch, einen Ansatz zu präsentieren, der genau in dieser Form umzusetzen ist, sondern vielmehr soll ein Beitrag zum wissenschaftlichen Diskurs geleistet werden, indem eine aktuelle wirtschaftsgeographische Problemstellung mit visuell-analytischen Methoden angegangen wird. Als Datengrundlage dieser Arbeit wird die im Laufe des letzten Jahrzehnts von NutzerInnen generierte, mittlerweile sehr umfangreiche und kostenlos auf dem Internet zugängliche Enzyklopädie Wikipedia eingesetzt (Wikipedia 2012). Die räumlich-zeitlichen Analysen mit Wikipedia von Hecht untermauern die Eignung von Wikipedia als geographische Datengrundlage und dienen als Ausgangspunkt für die vorliegende Untersuchung der Agglomerationsdefinition mit diesem nutzergenerierten Datensatz. Auf die zwei folgenden Fragestellungen wird dabei vertieft eingegangen. 1. Eignen sich die auf Wikipedia verfügbaren nutzergenerierten Inhalte, um mit modernen Methoden und Mitteln der Informationsvisualisierung und -analyse Agglomerationen zu identifizieren? 2. Welche Probleme treten in Verbindung mit den Raum- und Randeffekten in den Daten auf und welche Gebiete sind hauptsächlich betroffen davon?

Commuters have had an important role in shaping the spatial organization of Switzerland, as commuter flows have been one of the most significant criteria to delineate urban agglomeration zones. Even though urban areas and respective agglomerations have continuously gained in importance in Switzerland to this day, the Swiss national population census will no longer include commuter data at high spatial resolution. Hence, the definition of the rapidly evolving urban agglomeration concept will have to be modified for future urban research and planning purposes. We propose a crowdsourcing approach to overcome this data gap, and employ the open and web-based Wikipedia encyclopedia as a new resource to delineate agglomeration areas. Using the North Eastern parts of Switzerland in this case study, we systematically evaluate whether user-generated content can serve as an option to fill the commuter data gap in future Swiss national population censuses to define agglomeration areas. In a second step, we evaluate the influence of potential edge effects on our chosen approach. We employ the number of hyperlinks in the Wikipedia database to quantify the strength of functional relationships between municipalities appearing in the Wikipedia encyclopedia. Next, we visualize the extracted municipality network structure for the chosen study area. Finally, we cluster the connected municipalities to agglomeration zones, and compare the computed municipality clusters with the agglomeration areas currently defined by the Swiss census. Our results suggest that the aggregation structure of our crowdsourcing approach is congruent with the officially developed agglomeration areas proposed by the Swiss census. Crowdsourced data thus might be an additional future data resource to complement more traditional census statistics for space districting purposes or socio-economic research in urban geography and planning. However, our results also suggest that geographic space indeed influences even non-spatially organized, crowdsourced encyclopedic entries, and this must be systematically studied further in future studies.
Agglomerations newly defined with crowdsourced data. Visualizing North Eastern Switzerland based on Wikipedia content.
Keywords: Verdichtungsraum; Siedlungsstruktur; Verflechtungsbereich; Verstädterung; Stadtwachstum; Stadtregion; Agglomeration; Definition; Datengrundlage; Datensatz; Visualisierung